Hear him roar : a novel - Wingfield, Andrew, 1966- (UPCC book collections on Project MUSE., 2005)
A cougar attacks a jogger in the suburbs of a Western city. Charlie Sayers, a wildlife biologist facing retirement, is drawninto the search for the lion. He gets caught up in the conflict between wildlife habitat and an increasingly developed environment as, teetering between crisis and farce, he tries to piece together the puzzle of his own life.